1997
DOI: 10.4141/a96-097
|View full text |Cite
|
Sign up to set email alerts
|

Activity of intestinal mucosal membrane carbohydrases in cattle of different breeds

Abstract: . Activity of intestinal mucosal membrane carbohydrases in cattle of different breeds. Can. J. Anim. Sci. 77: 441-446. A study was conducted to determine differences in length of intestinal villi and crypts and activity of mucosal carbohydrases of several breeds of beef cattle. Tissue samples, from three locations in the small intestine, were obtained from heifers and steers of Wagyu (W) × Angus (W × A), W × Hereford (W × H) and W × Holstein (W × O) crossbred cattle and from Holstein, Parthenais and Piedmontes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 18 publications
(31 reference statements)
0
7
2
Order By: Relevance
“…A positive correlation was observed between maltase activity and the depth of ileal crypts (r = 0.588; P = 0.027; n = 14). In contrast to our findings Mir et al (1997) noted differences in lactase acitivity. These differences might have resulted from the relatively longer villi in some breeds which might have influenced overall nutrient absorption in the animals.…”
Section: Carbohydrase Activitiescontrasting
confidence: 99%
See 1 more Smart Citation
“…A positive correlation was observed between maltase activity and the depth of ileal crypts (r = 0.588; P = 0.027; n = 14). In contrast to our findings Mir et al (1997) noted differences in lactase acitivity. These differences might have resulted from the relatively longer villi in some breeds which might have influenced overall nutrient absorption in the animals.…”
Section: Carbohydrase Activitiescontrasting
confidence: 99%
“…Kreikemeier et al (1990) studied the activity of carbohydrate digesting enzymes in Holstein and Longhorn bulls and observed it to be influenced by the type of diet and the level of feed intake. Mir et al (1997) considered the length of villi and crypts and mucosal carbohydrase activity to be an important factor in nutrient absorption; they recorded differences in these parameters between different cattle breeds, of which Holstein bulls had the highest lactase activity and the longest villi in the middle part of the intestine. ABSTRACT: This study examined the effects of extensive and intensive feeding on the morphology of the gastrointestinal tract as well as on the level of carbohydrase activity in the small intestine of growing ca�le.…”
mentioning
confidence: 99%
“…However, although intestinal tissue mass are not changed, the capacity for nutrient assimilation may be affected by the nutrients supplied to the small intestine as shown for the Na-glucose co-transporter in lambs (ShiraziBeechey et al, 1991). The density and length of the villi and the density and depth of the crypts are indicators of nutrient absorption rate (Mir et al, 1997), and the proximal part of the small intestines was found to be most responsive to changes in type of concentrate consumed (Mir et al, 1997;Zitnan et al, 2003). In the present experiment, the sizes of villi and crypts were not affected by type of concentrate used, but the number of jejunal villi and crypts increased in calves-fed EXP compared with TRA.…”
Section: Discussioncontrasting
confidence: 41%
“…This fact was confirmed by the positive correlation between the morphometric parameters of ruminal and intestinal mucosa (Zitnan et al, 2003). Mir et al (1997) considered the length of villi and depth of crypts and mucosal carbohydrase activity as an important factor in nutrient absorption. The authors found differences in these parameters between different cattle breeds.…”
mentioning
confidence: 83%